THE LEVEL OF EFFECTIVENESS OF THE DEVELOPMENT OF SPIRITUAL AND MORAL QUALITIES OF YOUNGER SCHOOLCHILDREN BY MEANS OF TOURISM - Abdumannatov Elbek Abdumajitovich; Ravshanqulova Dilora Ravshanovna (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article analyzes approaches to the development and promotion of the spiritual and moral values and uniqueness of cultural heritage sites through cultural heritage objects and pilgrimage tourism. Methods of evaluating the impact of tourism activities on the cultural and spiritual aspects of heritage sites are examined. A conceptual model and recommendations are proposed for the development of sustainable pilgrimage tourism programs that help preserve and enhance the unique historical, cultural, and spiritual significance of heritage objects.